2015 International Conference on Unmanned Aircraft Systems (ICUAS) 2015
DOI: 10.1109/icuas.2015.7152424
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual third party risk model for personal and unmanned aerial vehicles

Abstract: A conceptual third party risk (TPR) model is developed, implemented, and tested to demonstrate the capability of determining the risk to the population in a metropolitan city exposed to personal aerial vehicles (PAVs) and unmanned aerial vehicles (UAVs) traffic operations. The conceptual model that is primarily based on the methodology and experience of risk modelling for conventional aircraft is modified and the parameters are adjusted suitable for a determination of risk in the arrival, departure and cruise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…8(a). In several research studies on UAV crash trajectory [21][22][23], it was found that the angle at which the UAV impacted the ground is not fixed, but a considerable part of them is approximately at 90°. Therefore, in the collision analysis, the collision angle is selected as 90°, as shown in Fig.…”
Section: Scenarios Of Simulation Suav Crash On Ground Vehicles and Co...mentioning
confidence: 99%
“…8(a). In several research studies on UAV crash trajectory [21][22][23], it was found that the angle at which the UAV impacted the ground is not fixed, but a considerable part of them is approximately at 90°. Therefore, in the collision analysis, the collision angle is selected as 90°, as shown in Fig.…”
Section: Scenarios Of Simulation Suav Crash On Ground Vehicles and Co...mentioning
confidence: 99%
“…Following the development of the undesirable event model, the next step involves the collection and population of the data. As highlighted by Aalmoes et al, 6 given that unmanned systems are in their early development stages, operational data needed to populate third party casualty models are lacking. Consequently, the data necessary to drive numerous risk models were approximated through various sources such as numerical distributions, 6, 23 manned aircraft failure rates, 4,6,11 and/or military unmanned or manned operational data.…”
Section: Data Populationmentioning
confidence: 99%
“…As highlighted by Aalmoes et al, 6 given that unmanned systems are in their early development stages, operational data needed to populate third party casualty models are lacking. Consequently, the data necessary to drive numerous risk models were approximated through various sources such as numerical distributions, 6, 23 manned aircraft failure rates, 4,6,11 and/or military unmanned or manned operational data. 10 The authors believe that, although such assumptions might be suitable for approximations or comparative studies of various future operational concepts, reliability data from manned aircraft operations do not provide an adequate baseline due to vast redundancy and configuration differences between manned and unmanned aircraft as well as the varying operational context (military vs. civilian aircraft).…”
Section: Data Populationmentioning
confidence: 99%
See 2 more Smart Citations